Profil Penyelesaian Soal Fungsi Komposisi dan Fungsi Invers Siswa Kelas XI SMA Negeri 1 Pamona Utara Ditinjau dari Kemampuan Matematika - Charlie Alva Basompe; Alfisyahra Alfisyahra; Rita Lefrida; Baharuddin Paloloang (Aksioma, 2026)
This study aims to describe the problem-solving process for composition and inverse functions using Polya's stages, based on the mathematical abilities of students at SMA Negeri 1 Pamona Utara. The results show differences in problem-solving approaches according to students' mathematical proficiency. (1) Students with high mathematical ability can accurately identify given and required information, assess the sufficiency of the available data, and understand the relationships between different pieces of information. They can also determine additional necessary information, utilize all essential data, and systematically plan their problem-solving process. Moreover, they are skilled in answering accurately and verifying their solutions by identifying errors. (2) Students with moderate mathematical ability exhibit similar skills in understanding problems and planning solutions. However, in inverse function problems, they struggle to apply systematic steps and are less precise in their answers. (3) Students with low mathematical ability can identify given information and its connections but are unable to develop an effective problem-solving strategy. They still face difficulties in structuring systematic steps to arrive at the correct solution.